2018
DOI: 10.1016/j.taap.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A (BPA) and bisphenol S (BPS) alter the promoter activity of the ABCB1 gene encoding P-glycoprotein in the human placenta in a haplotype-dependent manner

Abstract: Exposure to bisphenols (BPA and BPS) during pregnancy can significantly affect fetal development and increase risk of adverse health consequences, however the underlying mechanisms are not fully elucidated. In human placenta, the efflux transporter P-glycoprotein (P-gp), encoded by the ABCB1 gene, extrudes its substrates from the trophoblasts back into the maternal circulation. Alterations in levels of placental P-gp could therefore significantly affect fetal exposure to xenobiotics that are P-gp substrates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The BPA-substitute BPS was reported to alter the placental expression of the efflux transporter P-glycoprotein (P-gp), one of the main regulators of fetal exposure to xenobiotics encoded by the ABCB1 gene. Using CRL-1584 human trophoblast cell lines, Speidel and colleagues demonstrated that acute exposure to BPS (0.5 nM) induced a significant haplotype-dependent decrease in ABCB1 promoter activity, while chronic BPS exposure (0.3 nM) induced a significant haplotype-dependent promoter activity increase, thus dramatically impacting on P-gp levels and fetal exposure to xenobiotics coming from the maternal circulation [ 92 ]. Moreover, prenatal exposure to BPS (5 mg/kg/d) in C57BL/6 N mice was described to increase the susceptibility to high-fat-diet-induced adipogenesis in F1 male adult mice via the upregulation of PPAR-γ and its target genes [ 93 ].…”
Section: Edcs and Fetal Programmingmentioning
confidence: 99%
“…The BPA-substitute BPS was reported to alter the placental expression of the efflux transporter P-glycoprotein (P-gp), one of the main regulators of fetal exposure to xenobiotics encoded by the ABCB1 gene. Using CRL-1584 human trophoblast cell lines, Speidel and colleagues demonstrated that acute exposure to BPS (0.5 nM) induced a significant haplotype-dependent decrease in ABCB1 promoter activity, while chronic BPS exposure (0.3 nM) induced a significant haplotype-dependent promoter activity increase, thus dramatically impacting on P-gp levels and fetal exposure to xenobiotics coming from the maternal circulation [ 92 ]. Moreover, prenatal exposure to BPS (5 mg/kg/d) in C57BL/6 N mice was described to increase the susceptibility to high-fat-diet-induced adipogenesis in F1 male adult mice via the upregulation of PPAR-γ and its target genes [ 93 ].…”
Section: Edcs and Fetal Programmingmentioning
confidence: 99%
“…studies have focused on the effects of BPA in isolated human placenta lines and in term human placenta (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). A concern with using cells derived from human term tissues is that they fail to replicate the full range of placental responses associated with the critical early and midpregnancy periods (34).…”
Section: Significancementioning
confidence: 99%
“…Speidel and colleagues demonstrated that acute exposure to BPS (0.5 nM) induced a significant haplotype-dependent decrease in ABCB1 promoter activity in CRL-1584 human trophoblast cell lines. However, chronic BPS exposure (0.3 nM) induced a significant haplotype-dependent promoter activity increase, impacting P-gp levels and fetal exposure to xenobiotics coming from the maternal circulation [ 158 ].…”
Section: Hypothesis Of Different Mechanisms Leading To MDmentioning
confidence: 99%